Traditional cow-calf systems of the northern region of Santa Fe, Argentina: current situation and improvement opportunities = Sistemas de cría tradicionales de la región norte de Santa Fe, Argentina: situación actual y oportunidades de mejora - Gregoretti, Guillermina (2024)
Cow-calf systems are at the core of Argentina´s significant national beef industry. The objectives were: i) to characterize the productive state of traditional cow-calf systems, named BASE, from the northern region of Santa Fe province, ii) to identify technologies for the productive improvement of the BASE system, and iii) to quantify the productive and economic impact of the adoption of the identified technologies. To characterize the BASE system, the available published data were systematized and validated in a workshop with leading regional experts in the field. To identify the technologies for improvement, a survey was conducted among regional farm advisors. Finally, to quantify the impact of adopting improvements in the BASE system, a modelling study was conducted. The results showed that traditional cow-calf systems have low productive and reproductive efficiency (45 kg LW ha-1 year-1 and 48% weaning rate) and little adoption of herd management and forage production technologies. The technologies identified were grazing management, training of farmers and farm staff, and seasonal mating. The modelling study showed that improvements in the production and use of forage and herd management practices would increase beef production and the gross margin of the BASE system by 70% and 96%, respectively.